2019
DOI: 10.1590/2177-6709.24.2.073-080.oar
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between oral health-related quality of life, the need for orthodontic treatment and bullying, among Brazilian teenagers

Abstract: Introduction: Orthodontic treatment aims at oral health and restoration of function as main objectives, however, psychological and social effects end up being the main reason for the demand for treatment. Objective: To determine the association between the oral health-related quality of life (OHRQoL), the need for orthodontic treatment and bullying among Brazilian teenagers. Methods: This was a cross-sectional epidemiological study. To assess the malocclusion, the Dental Aesthetic Index was used. And the Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 27 publications
5
36
0
6
Order By: Relevance
“…Of them, 3066 studies were thereafter excluded according to the inclusion criteria. In the end, a total of 11 studies were included in this systematic review and meta-analysis [6,[38][39][40][41][42][43][44][45][46][47]. Figure 1 demonstrates the review process.…”
Section: Study Selectionmentioning
confidence: 99%
“…Of them, 3066 studies were thereafter excluded according to the inclusion criteria. In the end, a total of 11 studies were included in this systematic review and meta-analysis [6,[38][39][40][41][42][43][44][45][46][47]. Figure 1 demonstrates the review process.…”
Section: Study Selectionmentioning
confidence: 99%
“…In addition, poor dental aesthetics [ 26 ] and caries [ 27 – 29 ] have negative emotional and social effects on oral health-related quality of life because of their negative impact on self-esteem and self-concept. The history, frequency and consequences of bully victimization also affects oral health related quality of life [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present study revealed that dental malocclusion had noticeable negative psychosocial impacts on adolescents in Malaysia. Although similar findings have been reported worldwide (Bittencourt et al, 2017;Dalaie et al, 2018;Gatto et al, 2019), the present study applied a qualitative design, specifically focusing on patients presenting to two specialized dental clinics. Therefore, in addition to the negative influences of dental malocclusion on the emotion, social interaction and quality of life of patients in general, the present study provides insight into the pressure they received from different parties because of their conditions, which eventually resulted in their treatment-seeking decisions.…”
Section: Discussionmentioning
confidence: 55%
“…Similarly, children and adolescents with the similar condition were found to seek treatment, mainly because of their dissatisfaction with the dentofacial deformities, recommendations from dentists and the influence of schoolmates who wear braces (Chambers & Zitterkopf, 2019;Ernest et al, 2019). Gatto et al (2019) also reported that school bullying took place in 12.8% of adolescents with dental malocclusion, greatly affecting their selfesteem and oral health-related quality of life.…”
Section: Introductionmentioning
confidence: 99%